2007
DOI: 10.7326/0003-4819-146-8-200704170-00009
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis: Chondroitin for Osteoarthritis of the Knee or Hip

Abstract: Large-scale, methodologically sound trials indicate that the symptomatic benefit of chondroitin is minimal or nonexistent. Use of chondroitin in routine clinical practice should therefore be discouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
207
2
12

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 292 publications
(228 citation statements)
references
References 36 publications
7
207
2
12
Order By: Relevance
“…One example is that of conditionally recommending against the use of glucosamine and chondroitin sulfate for patients with knee OA. The TEP relied initially on the results of the Glucosamine/Chondroitin Arthritis Intervention Trial (40) and meta-analyses that demonstrated significant heterogeneity in effect size (41)(42)(43) coupled with the lack of availability of prescription-quality preparations evaluated and approved for the indication of OA by the FDA. This original decision was reaffirmed after reviewing the results of a more recent network meta-analysis that also failed to demonstrate clinically important efficacy for these agents (44).…”
Section: Discussionmentioning
confidence: 99%
“…One example is that of conditionally recommending against the use of glucosamine and chondroitin sulfate for patients with knee OA. The TEP relied initially on the results of the Glucosamine/Chondroitin Arthritis Intervention Trial (40) and meta-analyses that demonstrated significant heterogeneity in effect size (41)(42)(43) coupled with the lack of availability of prescription-quality preparations evaluated and approved for the indication of OA by the FDA. This original decision was reaffirmed after reviewing the results of a more recent network meta-analysis that also failed to demonstrate clinically important efficacy for these agents (44).…”
Section: Discussionmentioning
confidence: 99%
“…Chondroitin sulfate is a glycosaminoglycan involved in the formation of cartilage and other joint matrix structures. Evidence supporting the clinical benefits of chondroitin sulfate for the improvement of osteoarthritis symptoms is inconsistent (Reichenbach et al, 2007). In a recent meta-analysis of 10 large-scale placebo-controlled trials of chondroitin, glucosamine, or their combination (n = 3,803), Wandel and colleagues found that none of these therapies were associated with significant improvements in pain, as measured on a 10-cm visual analog scale, nor were they associated with any significant reduction in joint-space narrowing compared with placebo (Wandel et al, 2010).…”
Section: Dietary Supplementsmentioning
confidence: 99%
“…Various meta-analyses [Reichenbach et al 2007;Richy et al 2003;Leeb et al 2000 However, the largest trial, the GAIT study, reported no effect on these endpoints.…”
Section: Symptomatic Slow-acting Drug For Oa Effectsmentioning
confidence: 99%